Part of a proposal for Anmozj default for disclosure of accounting for corporate profits and returns of its shares Experimental study in the Iraqi market for securities - salah mahdi salih (Iraqi Journal for Administrative Sciences, 2025)
Dispite Accounting Disclosure of Corporations Income and its Stocks Return in External Financial Statement its an Important Requirement, So it is Expected to Have Exceptional Affect in Investors Decisions, Because this Assist in planning Their Investments in Future. The Aim of This Research is to Construct A Framework for Virtual Model of Accounting Disclosure about Income of Corporations and its Stockcs Return. The Research Apply on Asample of(12) Corporation listed in Iraqi Stock Exchange and This Corperations Distributed to (12) Industries (Manufacture Agriculture and Serrivce) The Research Conclude many Conclusions, The First one is Focus on Accounting Model Must be Construct depending on Advanced Scientific Models and also Depending on Financial Ratios and Indecators to Give A Suitable Accurance to Predict for Corporations Income and its Stocks Return